Penerapan Model Pembelajaran Kooperatif untuk Meningkatkan Kemampuan Siswa dalam Pembelajaran Drama di SMA Swasta Istiqlal Delitua - Nur Fatimah; Ratna Lolane Sianipar; Poppy Amalia; Stephanie Br Sipayung; Jesicha Nainggolan; Dia Ananda Putri; Safinatul Harahap; Nurul Azizah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study discusses the application of the cooperative learning model in improving students' ability to learn drama at Istiqlal Delitua Private High School. In this case, the cooperative learning model is one of the learning models used in drama learning because this model can encourage collaboration, improve social skills, and develop student creativity. This study also uses a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation. The results of the study show that the application of the cooperative learning model significantly improves student engagement, drama script writing skills, and character acting skills. This model is also effective in creating an interactive and fun learning atmosphere, increasing student motivation, and building confidence in drama performances. This study also emphasizes the importance of teacher support and a conducive environment in implementing a cooperative learning model for drama learning.